A sensitive LC‐MS/MS method for quantifying capsaicin and dihydrocapsaicin in rabbit plasma and tissue: application to a pharmacokinetic study. (4th August 2014) - Wang, Dimin; Meng, Fanhua; Yu, Lin; Sun, Lu.; Sun, Lili; Guo, Jifen
Abstract: Prescription and nonprescription products for topical management of pain, including cream, lotion and patch forms, contain capsaicin (CAP) and dihydrocapsaicin (DHC). There are few in vivo studies on absorption, bioavailability and disposition of CAP and DHC. We established a sensitive and rapid LC‐MS/MS assay to determine CAP and DHC levels in rabbit plasma and tissue. Bio‐samples prepared by liquid–liquid extraction using n ‐hexane–dichloromethane–isopropanol (100: 50: 5, v/v/v) mixture were separated by isocratic chromatography with an Extend C18 column. The mobile phase was acetonitrile–water–formic acid (70: 30: 0.1, v/v/v). The method was linear from 0.125 to 50 ng/mL for a 100 μL bio‐sample, and the lower quantification limit was 0.125 ng/mL. Total run time to analyze each sample was 3.5 min. We used this validated method to study pharmacokinetics and tissue distribution of CAP gel administered topically to rabbits. A very small amount of CAP and DHC was absorbed into the systemic circulation. The highest plasma concentration was 2.39 ng/mL, and the mean peak plasma concentration value after 12 h of CAP gel application was 1.68 ng/mL. Drug concentration in treated skin was relatively high, with low concentration in other tissues. Thus, topical CAP gel had strong local effects and weaker systemic effects. Copyright © 2014 John Wiley & Sons, Ltd.